[Re]Discovering the Grasslands: a visitor and community centre for Rhodes and the new Grasslands National Park in the highlands of the Eastern Cape - Schoeman, J. C. (University of the Free State, 2023)
Visitor centres within a specific landscape are conceived as powerful communicative tools, facilitating users' immersive experience in a distinct contextual setting. In the context of the village of Rhodes, which foresees a forthcoming increase in tourism, the village currently lacks the necessary infrastructure to accommodate and educate visitors about its unique environment. Regrettably, many local visitor centres often fall short of authentically capturing the essence of the landscape and its surrounding context through their architectural design, resulting in inauthentic reproductions of assumed vernacular architecture. This study explores multifaceted themes, including temporality, permanence, ecotourism, and critical regionalism, with its primary objective being the identification and subsequent integration of site-specific nuances into the architectural framework. This integration aims to effectively harmonise the design within the encompassing landscape while recognising and embracing the local inhabitants of the valley. The inception of the visitor centre's design can be traced back to an analysis of the natural environment, serving as the foundation for a range of conceptual explorations. These explorations were further enriched by precedent studies and firmly rooted within theoretical investigations. This design endeavour challenges conventional perceptions of an appropriate visitor centre. Instead of resisting its historical presence within the Victorian village, it aspires to deeply assimilate itself into the natural surroundings, ultimately aligning and coexisting with the landscape and the local population rather than opposing it.
Dissertation(M.Arch.(Architecture))--University of the Free State, 2023
Keywords: Visitor centres; Tourism--South Africa; Rhodes, South Africa; Ecotourism